The past, present and future of Alzheimer's disease – part 1: the past - Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
Background Alzheimer's disease (AD) was described in 1907, and since then it changed from a relatively rare condition to one of the most prevalent diseases.